Rastreamento ocular e resposta comportamental na avaliação e modificação do viés atencional em pessoas com sintomas de ansiedade social - Claudino, Rianne Gomes e (2022)
People with Social Anxiety Disorder (SAD) in social encounters tend to intensify attention to threatening stimuli. The attentional bias modification intervention (ABM) imposes a shift of attention to a non-threatening stimulus, which may lead to a decrease in SAD symptoms. In this study, we performed 2 studies, with 2 experiments each. In Study 1 (Experiments 1 and 2), the effects of social anxiety and an attentional bias modification task on eye tracking patterns were analyzed. In Experiment 1, subjects with symptoms of social anxiety disorder (SAD) and controls were subjected to a mild anxiogenic situation and watched scenes of anxiogenic or non-anxiogenic situations. Next, they observed trios of emotional faces and pairs of photographs with positive and negative social interactions. No difference was found between groups in amount and duration of fixations, which indicates that mild anxiogenic situations did not affect the ocular pattern of visual exploration. In Experiment 2, we sought to investigate changes in fixations after attentional bias modification (ABM) intervention in subjects with SAD symptoms. It was observed that, after the neutral ABM, there was a decrease in fixations only on disgust faces, and after the positive ABM there was a reduction in the duration of fixations only on the angry faces. Thus, it is understood that the attentional bias towards faces considered threatening (disgust and anger) for the SAD has changed. In Study 2 (Experiments 3 and 4), data collection was performed remotely. In Experiment 3, we sought to verify whether the correct answers and response time (RT) to brief emotional stimuli were altered after positive ABM. In the task, participants should indicate whether a particular face was present in the trio presented earlier, before and after the ABM. It was found that there was no difference between groups RT or correct answers. In Experiment 4, the same task as in Experiment 3 was used, increasing the exposure time of the trios from 2s to 5s. It was observed that, after ABM, the RT of the experimental group to negative faces decreased, which indicates that the participants became more reactive to negative expression. Taken together, it is concluded that, for the SAD, ABM can reduce the attentional bias of threatening faces in terms of eye tracking and reduce RT to negative emotions. In addition, it is understood that for the SAD the positive ABM works better than the neutral one.